Thermal behavior of cement based plastering mortar containing hybrid microencapsulated phase change materials - Kheradmand, Mohammad (2014)
Several studies have proven the energy savings associated to the incorporation of phase change materials (PCM) into plastering mortars for application in buildings, in view of thermal comfort. However, the simultaneous incorporation of more than one type of PCM (hybrid PCM) into plastering mortars may even bring about added benefits for the thermal efficiency as they can be tailored for specific performance targets. One of the aims of this paper is to demonstrate the feasibility of hybrid PCM mortars at the material level. This study encompasses the evaluation of several mortars with and without microencapsulated PCM. Hardened mortar samples were assessed through scanning electron microscopy (SEM), and also through differential scanning calorimetry (DSC). The DSC tests that were performed have demonstrated a clear dependence of the measured thermograms in regard to the adopted heating/cooling rate. Therefore, this research work also focused on this issue, both for single and hybrid PCM mortars. The following effects of heating/cooling cycles on DSC results were evaluated: the shape of the thermograms, the peak phase change temperature, the calculated specific enthalpy and the hysteretic behavior between heating and cooling cycles.